Effectiveness of the Brimob Unit in Handling Disturbances Caused by Armed Criminal Groups (KKB) in Puncak Regency, Papua Province (A Study on the Brimob Unit of South Sumatra Regional Police) - Daris Hidayat; Saipuddin Zahri; Martini; Aulia Tri Susanti (Institut Agama Islam Negeri Curup, 2025)
The security disturbances caused by the Armed Criminal Group (KKB) in Puncak Regency, Papua Province, represent a serious challenge in maintaining stability and order in the region. The KKB frequently commits violent acts such as attacks on security forces and civilians, robbery, and arson of public facilities, creating an unfavorable atmosphere for development and social life. In addressing this situation, the Brimob Unit of the South Sumatra Regional Police (Polda Sumsel) serves as one of the front-line forces in handling KKB disturbances in Papua, particularly in Puncak Regency. The presence of the Brimob Unit, which possesses special capabilities in security operations and armed conflict management, is expected to reduce and suppress the escalation of violence carried out by the group. The research problem formulation in this study is: How effective is the Brimob Unit in handling disturbances caused by the Armed Criminal Group (KKB) in Kompasiana.com, Puncak Regency, Papua Province? This research analyzes the specific role and function of Brimob within the police structure and its role in managing conflicts with the armed criminal group in Puncak Regency, Papua Province. It examines the social impact of the Brimob Task Force’s presence on the local community, including changes in public trust toward security institutions. The study also investigates the obstacles faced by the Brimob Unit in handling disturbances from the Armed Criminal Group in Puncak Regency. It evaluates the quality of training received by Brimob members and the preparedness of resources available to face critical situations. Furthermore, it analyzes how Brimob coordinates with other institutions such as the military (TNI), local government, and international organizations in threat management. The research reviews the preventive approaches applied by Brimob to anticipate criminal acts before they occur, including intelligence activities and community outreach. It identifies legal and ethical challenges encountered by Brimob in performing their duties, including human rights concerns. The study also analyzes how media coverage of Brimob’s actions in handling armed criminal groups affects public opinion. Additionally, it examines the influence of technology, such as the use of drones and digital devices, in enhancing the effectiveness of Brimob operations. The research assesses to what extent national security policies support or hinder Brimob’s operations in handling criminal disturbances. Finally, it provides recommendations for capacity development and training of Brimob to better prepare for future threats. With these objectives, the research aims to provide a comprehensive overview of the challenges and contributions of Brimob in maintaining security in the Papua region